SARS-CoV-2 Infection in Cancer Patients: Essential Aspects - Juan Santiago Serna Trejos; Stefanya Geraldine Bermúdez Moyano (Revista Finlay)
The global panorama generated by SARS-CoV-2 meant a wide deployment of new knowledge related to this virus, for multiple reasons, in the first instance, due to the great speed of its contagion, due to its relationship with high mortality rates associated, also adds the burden of disease that it entailed due to the lack of knowledge of an optimal approach or the lack of consensus by the different medical societies to achieve its treatment. The risk of SARS-CoV-2 infection in cancer patients is related to their immune status, which is greatly affected by their underlying cancer or tumor condition as well as the treatment itself.